Corruption in business — Are management attitudes right? - Pitt, Leyland F. (Journal of business ethics, 1986)
Corruption in business is as old as business itself. Corruption exists to some extent in all cultures, under all market systems and in all countries. The objectives of this paper are not to stand in judgement or to consider moral issues. This article considers the findings of a study concerning managerial attitudes towards corruption in business. The methodology involves a number of scenarios which could be construed as being deviant or dishonest. These are presented to respondents. Respondents are then asked questions regarding each situation. The findings were interesting. While the sample in general condemned corruption and corruptive practices, the perceived participation by the peer group was higher than one would have expected. The findings of a more comprehensive study of a similar nature should be meaningful to corporate policy in this regard, not only in respect of corruption, but also when decisions have to be made regarding the receipt of gifts.